Effects of Paracetamol, Amoxicillin, and their Combination on Male Rabbit Body and Organs Weight - Fayrouz Khaled; Fatma Abdulsalam (AlQalam Journal of Medical and Applied Sciences, 2024)
The administration of pharmaceuticals such as paracetamol (PAR) and amoxicillin (AMO) has been linked to physiological changes in animals. While these drugs are widely utilized for their therapeutic benefits, their potential effects on body and organ weights are not fully understood. Male rabbits were divided into four groups a control group, a group treated with PAR, a group treated with AMO, and a group receiving both drugs PAR+AMO. Body weight changes were monitored weekly, and organ weights (liver, lungs, heart, kidneys, testes, and brain) were measured at the end of the trial. Data were statistically analyzed, with significance set at p < 0.05. Body weight changes were observed across all treatment groups. In the control group, there were gradual weight increase from 1839±136.20g to 1975±89.94g, remaining consistent throughout the trial. While in the PAR group, we observed initial weight loss from 1667±43.83g to 1584±31.69g in week one, followed by recovery and reaching 1860±26.48g by week five. In the AMO group, there were a minor initial weight loss, followed by steady gains peaking at 2028±12.02g in week four, slightly decreasing to 2007±4.97g in week five. In the PAR+AMO group, we reported fluctuations in weight, starting at 1857±52.43g, peaking in week one (2001±94.50g), and ending at 1900±92.61g in week five. Organ weight analysis revealed significant changes. Liver and Lungs were notable increases in the PAR (73.214±5.006g liver; 8.356±0.663g lungs) and AMO groups (76.250±0.364g liver; 6.650±0.030g lungs). Combination therapy moderated these effects. Other Organs such as kidney, heart, brain, and testes weights showed no significant alterations (p > 0.05) across the groups. In conclusion, this study highlights the differential impact of PAR and AMO, individually and in combination, on body and organ weights in male rabbits. While PAR and AMO caused notable changes in liver and lung weights, combination therapy appeared to moderate these effects. Body weight fluctuations were observed across all groups, emphasizing the need for further investigation into the mechanisms underlying these physiological responses to pharmaceutical interventions. تم ربط إعطاء المستحضرات الصيدلانية مثل الباراسيتامول و المضاد الحيوي الأموكسيسيلين بالتغيرات الفسيولوجية في الحيوانات. في حين يتم استخدام هذه الأدوية على نطاق واسع لفوائدها العلاجية، إلا أن تأثيراتها المحتملة على أوزان الجسم والأعضاء ليست مفهومة تمامًا. تم تقسيم الأرانب الذكور إلى أربع مجموعات مجموعة التحكم، ومجموعة عولجت بالباراسيتامول ، ومجموعة عولجت بالأموكسيسيلين ، ومجموعة تلقت كلا العقارين الباراسيتامول والاموكسيسلين. تمت مراقبة تغيرات وزن الجسم أسبوعيًا، وتم قياس أوزان الأعضاء (الكبد والرئتين والقلب والكلى والخصيتين والدماغ) في نهاية التجربة. تم تحليل البيانات إحصائيًا، مع تحديد الأهمية عند p < 0.05. تم ملاحظة تغيرات في وزن الجسم في جميع مجموعات العلاج مجموعة التحكم زيادة تدريجية في الوزن من 1839±136.20 جرام إلى 1975±89.94 جرام، وظلت ثابتة طوال التجربة. مجموعة الباراسيتامول تم فقدان الوزن الأولي من 1667±43.83 جرام إلى 1584±31.69 جرام في الأسبوع الأول، تلا ذلك التعافي والوصول إلى 1860±26.48 جرام بحلول الأسبوع الخامس. مجموعة الاموكسيسلين تم فقدان الوزن الأولي البسيط، يليه مكاسب ثابتة بلغت ذروتها عند 2028±12.02 جرام في الأسبوع الرابع، ثم انخفضت قليلاً إلى 2007±4.97 جرام في الأسبوع الخامس. مجموعة الباراسيتامول والاموكسيسلين حدثت تقلبات في الوزن، بدءًا من 1857±52.43 جرام، وبلغت ذروتها في الأسبوع الأول (2001±94.50 جرام)، وانتهت عند 1900±92.61 جرام في الأسبوع الخامس. كشف تحليل وزن الأعضاء عن تغييرات كبيرة في الكبد والرئتين نلاحظ زيادات ملحوظة في مجموعات الباراسيتامول (73.214 ± 5.006 جم الكبد؛ 8.356 ± 0.663 جم الرئتين ومجموعات الاموكسيسلين 76.250 ± 0.364 جم الكبد؛ 6.650 ± 0.030 جم الرئتين. خفف العلاج المركب من هذه التأثيرات. لم تظهر أوزان الكلى والقلب والدماغ والخصيتين أي تغييرات كبيرة (ص> 0.05) عبر المجموعات. وفي الختام، تسلط هذه الدراسة الضوء على التأثير التفاضلي للباراسيتامول والاموكسيسلين ، بشكل فردي وبالاشتراك، على أوزان الجسم والأعضاء لدى ذكور الأرانب. وفي حين تسبب الباراسيتامول والاموكسيسلين في حدوث تغييرات ملحوظة في أوزان الكبد والرئة، بدا أن العلاج المركب يخفف من هذه التأثيرات. ولوحظت تقلبات في وزن الجسم في جميع المجموعات، مما يؤكد الحاجة إلى مزيد من التحقيق في الآليات الكامنة وراء هذه الاستجابات الفسيولوجية للتدخلات الصيدلانية